The long non-coding RNA Cerox1 is a post transcriptional regulator of mitochondrial complex I catalytic activity - Tamara M Sirey; Kenny Roberts; Wilfried Haerty; Oscar Bedoya-Reina; Sebastian Rogatti-Granados; Jennifer Y Tan; Nick Li; Lisa C Heather; Roderick N Carter; Sarah Cooper; Andrew J Finch; Jimi Wills; et al. (eLife)
To generate energy efficiently, the cell is uniquely challenged to co-ordinate the abundance of electron transport chain protein subunits expressed from both nuclear and mitochondrial genomes. How an effective stoichiometry of this many constituent subunits is co-ordinated post-transcriptionally remains poorly understood. Here we show that Cerox1, an unusually abundant cytoplasmic long noncoding RNA (lncRNA), modulates the levels of mitochondrial complex I subunit transcripts in a manner that requires binding to microRNA-488-3p. Increased abundance of Cerox1 cooperatively elevates complex I subunit protein abundance and enzymatic activity, decreases reactive oxygen species production, and protects against the complex I inhibitor rotenone. Cerox1 function is conserved across placental mammals: human and mouse orthologues effectively modulate complex I enzymatic activity in mouse and human cells, respectively. Cerox1 is the first lncRNA demonstrated, to our knowledge, to regulate mitochondrial oxidative phosphorylation and, with miR-488-3p, represent novel targets for the modulation of complex I activity.